(untitled) (Siddhajyoti Interdisciplinary Journal, 2024)
The centrality of reading in students’ academic performance has been well-established in the literature. As a learned skill, reading is acquired in an instructional setting and students’ ability to comprehend and interact with texts is largely shaped by reading instruction. The efficacy of reading instruction is subject to varied factors that stand as challenges to be overcome. This study aimed to explore the challenges experienced by university teachers in teaching reading to B.Ed. English major students. To this end, the study adopted a case study design that comprised purposively selected four university English teachers teaching English reading courses at a constituent campus of Tribhuvan University, and eight B.Ed. English majors from the same campus. The data were collected through a combination of three qualitative methods: classroom observation, semi-structured interview and focus group discussion. The findings revealed students having no coursebooks and relying on other substandard reading materials, students’ poor reading habits, students’ limited vocabulary knowledge, strategically untrained students, and the length of courses and texts as major challenges faced by teachers in teaching the prescribed reading courses. Drawing on these findings, implications for reading pedagogy are considered.